WOMEN «ARE A MYSTERY». LESBIANS AS AN ENIGMATIC SUBJECT FOR THE COSTA RICAN PRESS BETWEEN 1985 AND 1999 - Sequeira Rovira, Paula (2023)
This work is an attempt to deepen on the issue of perceptions about lesbians and about women who had erotic encounters with other women that appeared in the news between 1985 and 1999. It was found that although the perception of them was diffuse, there was a greater delimitation towards their image. However, this perception assumed the lesbian to be a white, sensual, young, tall, thin woman, and without any visible disability. A second aspect that was found was the use of sex between women as a strategy to promote the sale of certain products or as part of the sexual trade within Costa Rican territory. Finally, some perceptions about lesbians that existed because of a feminist activity organized in 1990 are analyzed. The aim of this work is to analyze the narratives about lesbians or women who had sex with other women to determine what type of messages were linked to that content.